Jan Čep: What Ruralism? Some Comparisons Between "Čep's Writing" and Francophone Tradition - Galmiche, Xavier (Bohemica Olomucensia, 2015)
The study attempts to compare Jan Čep's literary work with francophone "ruralist" authors (mainly Henri Pourrat, but also Jean Giono, Henri Bosco, Swiss Charles-Ferdinand Ramuz - he was in direct contact with several of them before his emigration to France and during his exile). Although they share many features typical of rural narrative (a lyrical evocation of natural elements, drastic viewing of psychological and social dramas), Čep distances himself very clearly from the temptations of a pagan vision that brought this group closer to a cultural programme of the conservative, even reactionary France. This distance can be partly explained by Čep's temperament, but also reflects the Czech tradition of rural literature.
Keywords: Jan Čep's literary works; ruralism; French writers; rural narrative